Equilibrium Thermodynamics, Formation, and Dissociation Kinetics of Trivalent Iron and Gallium Complexes of Triazacyclononane-Triphosphinate (TRAP) Chelators: Unraveling the Foundations of Highly Selective Ga-68 Labeling - Vágner, Adrienn; Forgács, Attila; Brücher, Ernő; Tóth, Imre; Maiocchi, Alessandro; Wurzer, Alexander; Wester, Hans-Jürgen; Notni, Johannes; Baranyai, Zsolt (Frontiers in Chemistry, 2018)
In order to rationalize the influence of FeIII contamination on labeling with the 68Ga eluted from 68Ge/68Ga-generator, a detailed investigation was carried out on the equilibrium properties, formation and dissociation kinetics of GaIII- and FeIII-complexes of 1,4,7-triazacyclononane-1,4,7-tris(methylene[2-carboxyethylphosphinic acid]) (H6TRAP). The stability and protonation constants of the [Fe(TRAP)]3− complex were determined by pH-potentiometry and spectrophotometry by following the competition reaction between the TRAP ligand and benzhydroxamic acid (0.15 M NaNO3, 25°C). The formation rates of [Fe(TRAP)] and [Ga(TRAP)] complexes were determined by spectrophotometry and 31P-NMR spectroscopy in the pH range 4.5–6.5 in the presence of 5–40 fold HxTRAP(x−6) excess (x = 1 and 2, 0.15 M NaNO3, 25°C). The kinetic inertness of [Fe(TRAP)]3− and [Ga(TRAP)]3− was examined by the trans-chelation reactions with 10 to 20-fold excess of HxHBED(x−4) ligand by spectrophotometry at 25°C in 0.15 M NaCl (x = 0,1 and 2). The stability constant of [Fe(TRAP)]3− (logKFeL = 26.7) is very similar to that of [Ga(TRAP)]3− (logKGaL = 26.2). The rates of ligand exchange reaction of [Fe(TRAP)]3− and [Ga(TRAP)]3− with HxHBED(x−4) are similar. The reactions take place quite slowly via spontaneous dissociation of [M(TRAP)]3−, [M(TRAP)OH]4− and [M(TRAP)(OH)2]5− species. Dissociation half-lives (t1/2) of [Fe(TRAP)]3− and [Ga(TRAP)]3− complexes are 1.1 × 105 and 1.4 × 105 h at pH = 7.4 and 25°C. The formation reactions of [Fe(TRAP)]3− and [Ga(TRAP)]3− are also slow due to the formation of the unusually stable monoprotonated [*M(HTRAP)]2− intermediates [*logKGa(HL) = 10.4 and *logKFe(HL) = 9.9], which are much more stable than the [*Ga(HNOTA)]+ intermediate [*logKGa(HL) = 4.2]. Deprotonation and transformation of the monoprotonated [*M(HTRAP)]2− intermediates into the final complex occur via OH−-assisted reactions. Rate constants (kOH) characterizing the OH−-driven deprotonation and transformation of [* Ga(HTRAP)]2− and [*Fe(HTRAP)]2− intermediates are 1.4 × 105 M−1s−1 and 3.4 × 104 M−1s−1, respectively. In conclusion, the equilibrium and kinetic properties of [Fe(TRAP)] and [Ga(TRAP)] complexes are remarkably similar due to the close physico-chemical properties of FeIII and GaIII-ions. However, a slightly faster formation of [Ga(TRAP)] over [Fe(TRAP)] provides a rationale for a previously observed, selective complexation of 68GaIII in presence of excess FeIII.